Design principle of MoS2/C heterostructure to enhance the quantum capacitance for supercapacitor application. (15th December 2021) - Kapse, Samadhan; Benny, Bennet; Mandal, Pranab; Thapa, Ranjit
Highlights: Role of underneath carbon surface to enhance the quantum capacitance of MoS2 . The underneath CNT is identified for the phase transition of 1T-MoS2 to 1T′-MoS2 . Origin of enhanced density of states in MoS2 /C are studied through work functions. 1T′-MoS2 /3NV_CNT model is identified as an ideal electrode with CQ of 510 μF/cm 2 . Abstract: 1T Molybdenum disulfide (1T-MoS2 ) has been widely studied experimentally as an electrode for supercapacitors due to its excellent electrical and electrochemical properties. Whereas the capacitance value in MoS2 is limited due to the lower density of electrons near the Fermi level, and unable to fulfill the demand of industry i.e. quantum capacitance preferably higher than 300 μF/cm 2 . Here, we investigated the performance of 2H, 1T, and 1T′ phases of MoS2 in its pristine form and heterostructures with carbon-based structures as an electrode in the supercapacitors using density functional theory. Specifically, we reported that the underneath carbon nanotube (CNT) is responsible for the structural phase transition from 1T to 1T′ phase of MoS2 monolayer in 1T′-MoS2 /CNT heterostructure. This is the main reason for a large density of states near Fermi level of 1T′-MoS2 /CNT that exhibits high quantum capacitance (CQ ) of 500 μF/cm 2 at a potential of 0.6 V. Also, we observed that the nitrogen doping and defects in the underneath carbon surface amplify the CQ of heterostructure for a wider range of electrode potential. Therefore, the 1T′-MoS2 /N doped CNT can be explored as an electrode for next-generation supercapacitors. Graphical abstract: Image, graphical abstract